OBTAINING MASCULINITY IN AYỌ̀BÁMI ADÉBÁYỌ̀’S NOVEL STAY WITH ME (2016) - Arif Rahman; Kurnia Ningsih (English Language and Literature, 2019)
This article about the analysis of a novel Stay With Me (2016) by Ayọ̀bámi Adébáyọ̀. The problem of this analysis focuses on the issue of obtaining masculinity. The aim of analyses is to find out how far the characters Akin and Dotun exposes the issue of obtaining masculinity. This analysis involved fictional devices such as character, plot (conflict), and setting to reveal the issue of obtaining masculinity in the novel. The analysis deals with the concepts of Patriarchy by Roger Horrocks that is supported by the text and context based interpretation. The result of this analysis shows that the protagonist are Nigerian men who attain his authority to obtain masculinity. Both characters become arrogant, compromised, and obsession. These can be seen by their cunning way to obtaining masculinity.